2013
DOI: 10.1021/es402169d
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Reduced Sulfur Compounds on Pd-Catalytic Hydrodechlorination of Trichloroethylene in Groundwater by Cathodic H2under Electrochemically Induced Oxidizing Conditions

Abstract: Reduced sulfur compounds (RSCs) poison Pd catalysts for catalytic hydrodechlorination of contaminants in anoxic groundwater. This study investigates the effects of RSCs on Pd-catalytic hydrodechlorination of trichloroethylene (TCE) in oxic groundwater. Water electrolysis in an undivided electrolytic cell is used to produce H2 for TCE hydrodechlorination under oxidizing conditions. TCE is efficiently hydrodechlorinated to ethane, with significant accumulation of H2O2 under acidic conditions. Presence of sulfide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 50 publications
(191 reference statements)
1
17
0
Order By: Relevance
“…Moreover, chloride ions are a major byproduct of TCE degradation by PV3A-nZVI. According to previous studies [42,43] and our findings, the proposed pathways for the reductive dechlorination of TCE are displayed in Fig. 10.…”
Section: Tce Degradation Products and Pathwayssupporting
confidence: 66%
See 2 more Smart Citations
“…Moreover, chloride ions are a major byproduct of TCE degradation by PV3A-nZVI. According to previous studies [42,43] and our findings, the proposed pathways for the reductive dechlorination of TCE are displayed in Fig. 10.…”
Section: Tce Degradation Products and Pathwayssupporting
confidence: 66%
“…Only a few reports have evaluated the degradation products of TCE using the photochemical method [42] and a Pd-catalytic approach [43]. Jung et al [42] investigated the photochemical degradation of TCE through sulfite-mediated UV irradiation and found that degradation byproducts included 1,1-dichloroethylene (1,1-DCE), cis-DCE, trans-DCE, vinyl chloride (VC), chloroacetylene, ethylene, and ethane.…”
Section: Tce Degradation Products and Pathwaysmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides, addition of FeSO 4 to a TCE solution resulted in a negligible TCE removal . Direct oxidation of TCE on the MMO anode was also not favored because of the low overpotential for O 2 evolution (Scialdone et al, 2008), as evidenced in our previous investigation (Yuan et al, 2013a). In contrast, it has been reported that TCE can be reduced by the MMO cathode, showing dependence on the applied potential (Petersen et al, 2007).…”
Section: Feasibility Tests In the Labmentioning
confidence: 58%
“…Without current applied to the iron anode (20/0), TCE was only reduced by 25.3% within 4 h; when 5 mA current was applied to the iron anode (15/5), the removal increased to 66.0%; and when the applied current further increased, the removal efficiency stabilized at about 79.5%. Previous studies showed that TCE degradation shifted from reductive dechlorination in the absence of Fe(II) to OH oxidation in the presence of Fe(II) under acidic conditions, but OH oxidation was negligible at the pH above 6 because the generation of H 2 O 2 was limited and most Fe(II) was precipitated (Liao et al, 2013;Yuan et al, 2013aYuan et al, , 2012. Therefore, hydrodechlorination mechanism predominated for TCE degradation under the neutral circumstance in this work.…”
Section: Feasibility Tests In the Labmentioning
confidence: 59%